Analisis Kejadian Gempa Bumi Tektonik di Wilayah Pulau Sumatera - Jose Rizal; Sigit Nugroho; Adi Irwanto; , Debora (Jurnal Matematika, 2016)
The purpose of this study to get an overview of the earthquakes in Sumatra. The method used is descriptive statistics and models Autoregressive Fractionally Integrated Moving Average (ARFIMA). The result from analysis data yielded a mathematical model to predict the amount of tectonic earthquakes that occur every month in Sumatra is ARFIMA (4,0.350,3) with a value of RMSE is 0,040??. While the best model for the average magnitude of the many tectonic earthquakes that occur every month in Sumatra is ARFIMA (1,0.310,3) with a value of RMSE is 0.013. Based on the model results obtained forecast frequency earthquake and the average magnitude for the three periods ahead, namely the first period 21 times with an average magnitude is 4,91 SR , the second period will occur 14 times with an average magnitude is 4.94 SR and the third period will occur 20 times with an average magnitude is 4,96 SR.